PENGARUH PENGAWASAN, LINGKUNGAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT LANGSA LAMA - Lerdi Yanti Sigalingging; Muhammad Rizqi Zati; Dhian Rosalina (Niagawan, 2023)
This study aims to determine the influence of supervision, work environment, and organizational commitment on employee performance at the Langsa Lama District Office. This research uses quantitative methods. The analytical method used is the multiple linear regression method. The sample in this study was 52 people, using a saturated sampling method, where the entire population would be sampled. In this research, data collection uses interview and questionnaire techniques, where the questionnaire has been tested for validity and reliability. The results of the t test on the supervision variable have an insignificant influence on employee performance at the Langsa Lama District Head Office, the work environment variable has a positive and significant influence on employee performance at the Langsa Lama District Head Office, and the organizational commitment variable has a positive and significant influence on employee performance at the Langsa Lama Subdistrict Office. The results of the F test simultaneously have a significant influence on employee performance at the Langsa Lama District Head Office. The conclusion of this research is that the low level of supervision that occurs at the Langsa Lama Subdistrict Office will result in performance decreasing, thereby causing the goals of the agency to not be achieved, therefore it is very necessary for leaders to be firm and pay attention to each employee's performance, and so Also, the working environment at the Langsa Lama District Head's Office is very good, where the conditions in the agency are all conducive and comfortable, so this is able to increase employees to obtain even better performance, and the organizational commitment that every employee of the Office has. The Langsa Lama sub-district head is in the high category, this can be seen from the contribution and readiness of the employees to carry out their work which is always completed well and the level of employee desire to always stay with the agency is very large.  Keywords: Supervision, Work Environment, Organizational Commitment, Employee Performance